2011
DOI: 10.1158/0008-5472.can-11-2104
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia Induces Escape from Innate Immunity in Cancer Cells via Increased Expression of ADAM10: Role of Nitric Oxide

Abstract: One key to malignant progression is the acquired ability of tumor cells to escape immune-mediated lysis. Whereas tumor hypoxia is known to play a causal role in cancer metastasis and resistance to therapy, the link between hypoxia and immune escape in cancer remains poorly understood. Here, we show that hypoxia induces tumor cell resistance to lysis mediated by immune effectors and that this resistance to lysis occurs via a hypoxiainducible factor-1 (HIF-1)-dependent pathway linked to increased expression of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
135
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 28 publications
(26 reference statements)
6
135
0
5
Order By: Relevance
“…The present and previous studies (18,19) show that hypoxia decreases the susceptibility of tumor cells by reducing the expression of cell surface MICA, although the mechanisms of the reduction in the expression of cell surface MICA differ. Hypoxia has been reported to attenuate the antitumor activity of cytotoxic immune cells (17).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The present and previous studies (18,19) show that hypoxia decreases the susceptibility of tumor cells by reducing the expression of cell surface MICA, although the mechanisms of the reduction in the expression of cell surface MICA differ. Hypoxia has been reported to attenuate the antitumor activity of cytotoxic immune cells (17).…”
Section: Discussionsupporting
confidence: 55%
“…Several studies have shown that hypoxia-induced inhibition of NO production is linked to hypoxia-induced tumor invasion, metastasis, resistance to chemotherapy and shedding of cell surface MICA (18)(19)(20)(21)(22). In this study, hypoxia also induced the inhibition of NO production in osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…NO suppresses MMP-9 expression by destabilizing its mRNA in rat mesangial cells (35), whereas inhibition of NOS has been found to promote cytokine-induced MMP-9 expression in aortic smooth muscle cells (36) and exotoxin-mediated MMP expression in iNOS -/-mice (37). Furthermore, NO may inhibit hypoxia-induced expression of ADAM10 (38). Therefore, it is hypothesized that NO may affect the expression of other ADAMs, including ADAM12.…”
Section: Effects Of Nitric Oxide Synthase Deficiency On a Disintegrinmentioning
confidence: 99%